Bridging the Training-to-Classroom Gap: A Kirkpatrick Evaluation of Teacher Professional Development in Rural Indonesia - Zikri Rakhman; Muh Yusup (International Journal of Educational Qualitative Quantitative Research, 2026)
While global investments in teacher professional development (TPD) have surged, the "training-to-classroom" gap remains a persistent challenge in under-resourced, rural settings. This study evaluates the systemic impact of three primary TPD modalities, comprising formal certification (PPG), decentralized teacher working groups (MGMP), and centralized in-service workshops (Diklat), on instructional quality by utilizing Kirkpatrick’s Four-Level Evaluation Model. Adopting a qualitative bounded case study design centered in East Lombok as a region emblematic of the infrastructural and pedagogical challenges in rural Indonesia, data were generated from 38 key educational stakeholders through semi-structured interviews, 48 rigorous classroom observations, and systematic document analysis. The findings unpack a non-linear decoupling across Kirkpatrick’s evaluative levels. While TPD initiatives successfully generated positive teacher reactions (Level 1) and conceptual knowledge gains (Level 2), behavioral transfer into actual classroom practice (Level 3) was severely bottlenecked by rigid institutional accountability, resource scarcity, and generic program designs. Crucially, measurable improvements in teaching quality (Level 4) did not occur linearly but were ecologically contingent upon active principal instructional leadership and localized peer-learning networks, with the decentralized MGMP model showing the highest adaptive potential. Ultimately, this study challenges the linear efficacy assumptions of standardized TPD models in the Global South, demonstrating that professional growth in rural contexts is structurally mediated. It offers a socio-contextual framework for policy-makers to transition from standardized in-service training toward school-embedded, leadership-supported professional development ecosystems.